Inflation welfare cost analysis for Pakistan: An ARDL approach - Shahid Iqbal; Maqbool H. Sial; Najam Ul Hassan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Substantial changes in price inflation rate have serious economic consequences on the welfare of consumers in an economy but the issue has not, thoroughly, been reckoned in Pakistan. The study aims at assessing the nature and extent of welfare cost of inflation (WCI), employing well-established theory of money demand for the purpose. To address the issue more deeply, high frequency biannual series of gross domestic product (GDP) have been constructed and used benefitting from earlier works, a la Arby (2008). Biannual Divisia monetary aggregate (DMA) M2 series has, specifically, been constructed along with simple sum monetary aggregate (SSMA) M2 to establish the adequacy of DMA over SSMA in measuring the WCI in the long run based on versatile money demand specifications estimated using autoregressive distributed lag model (ARDL) framework. Short-term interest rates are regressed on money income ratios for Pakistan as implied by the theory. Based on information criteria, it is shown that DMAs rendered better fit and reliable estimates and log-log specification better approximate money demand than theirs counterparts. It is found that a decrease in inflation rate from 15 to 5 percent amounts to an annual welfare gain in the range of rupees 105 to 118 billion with log-log specification entailing one of the DMA or SSMA. These estimates of WCI are actually much less than the true inflation costs borne by an economy as moral inflation costs such as corruption, suicide attempts due to joblessness, political instability, currency devaluations etc. cannot be accounted for due no concrete measurability for these attributes. The study concludes that price stability on lower prices inflation rate must be the prime goal in monetary policy, and if the government spends a few billion rupees on price stability, it will gain too much not only in lowering the rampant corruption but also in gain political, moral, and financial stability. The study recommends the construction, publication, and use of high frequency DMAs and GDP series by the SBP that will opens many avenues for further improvements in evaluating WCI.
Keywords: 330; Welfare cost of inflation (WCI); Divisia monetary aggregate (DMA); simple sum monetary aggregate (SSMA); log-log form; autoregressive distributed lag (ARDL); Pakistan